2019
DOI: 10.1093/ndt/gfz076
|View full text |Cite
|
Sign up to set email alerts
|

Principles and strategies for involving patients in research in chronic kidney disease: report from national workshops

Abstract: Background There is widespread recognition that research will be more impactful if it arises from partnerships between patients and researchers, but evidence on best practice for achieving this remains limited. Methods We convened workshops in three Australian cities involving 105 patients/caregivers and 43 clinicians/researchers. In facilitated breakout groups, participants discussed principles and strategies for effective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…r e v i e w S Luo and ME Grams: Epidemiology research in kidney disease conduct of research studies, and the personalization of tools for CKD self-management such as smartphone applications. [112][113][114][115][116][117] Global initiatives are ongoing to reduce barriers to patient involvement in epidemiology research, such as patient uncertainty over their role in study design and guideline development and concerns from the academic community. 116,118,119 In Australia, the Standardized Outcomes in Nephrology initiative outlined practical steps to systematically implement consumer engagement in the management and research of kidney disease and to establish a set of core outcome measures on the basis of the shared priorities of patients, caregivers, clinicians, researchers, and policymakers.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…r e v i e w S Luo and ME Grams: Epidemiology research in kidney disease conduct of research studies, and the personalization of tools for CKD self-management such as smartphone applications. [112][113][114][115][116][117] Global initiatives are ongoing to reduce barriers to patient involvement in epidemiology research, such as patient uncertainty over their role in study design and guideline development and concerns from the academic community. 116,118,119 In Australia, the Standardized Outcomes in Nephrology initiative outlined practical steps to systematically implement consumer engagement in the management and research of kidney disease and to establish a set of core outcome measures on the basis of the shared priorities of patients, caregivers, clinicians, researchers, and policymakers.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%
“…[112][113][114][115][116][117] Global initiatives are ongoing to reduce barriers to patient involvement in epidemiology research, such as patient uncertainty over their role in study design and guideline development and concerns from the academic community. 116,118,119 In Australia, the Standardized Outcomes in Nephrology initiative outlined practical steps to systematically implement consumer engagement in the management and research of kidney disease and to establish a set of core outcome measures on the basis of the shared priorities of patients, caregivers, clinicians, researchers, and policymakers. 113,120 In Canada, the New Investigators in the Kidney Research Scientist Core Education and National Training Program engages patients in research to improve kidney disease outcomes and to promote the use of patient-reported outcome measures in kidney practice.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%
“…5 There have also been collaborative efforts to identify principles and strategies for effective consumer involvement in chronic kidney disease research, including clinical trials. 6 Although there are many benefits to consumer engagement, there are also a number of barriers that need to be overcome to ensure a smooth collaborative process. These obstacles include access to training, resources and educational opportunities for both researchers and consumers, reimbursement for consumers to attend meetings and scientific conferences (including registration, travel, accommodation, and meals), and appropriate access to technology for consumers to connect with other members of the research team.…”
Section: Consumer Engagementmentioning
confidence: 99%
“…13 It is increasingly recognized that a patient-centered approach in kidney disease must occur to improve patient education and outcomes. [14][15][16][17][18][19][20] End-Stage Kidney Disease (ESKD) is a chronic illness that occurs when kidneys stop working and is usually caused by diabetes and hypertension. 21 ESKD is an international and American public health crisis.…”
Section: Introductionmentioning
confidence: 99%